Answer:
y=-5x-36
Step-by-step explanation:
-66-(-61)= -5
6-5= 1
-5/1= -5
Y=-5x + B
-66= -5(6) + B
-66= -30 + B
-66 + 30 = (-30 +30) + B
-36 = B
Y= -5x-36
The answer C make more sense.
The quadratic formula is above.
You want each equation in standard form: ax^2 + bx + c = 0
I begin each problem by defining variables.
For instance 3. Is in standard form. X^2 -2x - 3 = 0. a = 1, b = -2, c = -3
Now use quadratic formula: x = [- b + or - sqrt(b^2 - 4ac)]\2a
More members prefer a beach vacation and a ski vacation than a cruise vacation
Answer:
1.668x10^13
Step-by-step explanation: